Factors affecting choice of delivery amongst patients and doctors and fetomaternal outcome in breech presentation in two large hospitals in malaysia - Bheena, Vyshali (2011)
Breech presentation is defined as a fetus in longitudinal lie with the fetal buttocks or lower extremities at the pelvic brim. Although its low incidence towards term, breech presentation and its management still remains a controversy till date. Data from the annual report in Hospital Tuanku Jaa’far Seremban (2007) shows a breech delivery rate of 91% via caesarean section compared to 39% in HUSM in the same year .This clearly points that there is difference in contributing factors among both patients and doctors involved in decision making in breech delivery in these two hospitals within two different regions in Malaysia itself.